Theorizing the relations between space and waste: residents’ insights on recycling practices and waste pickers in Vaalpark, Sasolburg - Pholoto, Lethabo (My University, 2018)
Separation at source has emerged as the method of choice for municipal recycling programmes, both in South Africa and around the world. At the same time, many local governments are seeking to engage and integrate waste pickers into the municipal waste and recycling systems. While a number of studies analyse the experiences of waste pickers in these processes, scant attention has been paid to residents. Yet the success of separation at source is dependent on resident participation, and such participation is notoriously difficult to secure. Given the generalised stigmatisation of waste pickers around the world, it is important to understand how including waste pickers in separation at source could affect resident participation. This research project therefore sought to understand the role of relations between residents and waste pickers in the implementation of a separation-at-source programme run by the Ikageng-Ditamating cooperative of waste pickers in the upmarket, historically white Vaalpark neighbourhood of Sasolburg, South Africa. Based on participant observation, observation, focus groups, semi-structured interviews and documentary analysis, this dissertation establishes that although the semi-formalised cooperative members based at the Vaalpark Recycling Centre are the only waste pickers who are meant to collect recyclables from the residents, independent informal street pickers still collect from the same homes, and informal landfill pickers also salvage materials sent the landfill. The dissertation argues that the ways the residents relate to the Ikageng-Ditamating cooperative of semi-formalised waste pickers and how they participate in the separation at source programme are informed by their relationships with and understandings of landfill and street waste pickers, as well as with their direction engagements with the cooperative waste pickers. The spaces that waste pickers work in play a crucial role in shaping the ways in which they work and relate to residents, the ways they are seen and understood, and how residents participate in separation at source. So do articulations of race, class, and space. Existing literature does not sufficiently explore how the spaces where waste pickers work contribute to the development of different kinds of waste pickers and their relations with residents. By engaging with Henry Lefebvre’s theory of the production of space, this dissertation contributes to literatures both on resident participation in separation at source and the relationship between residents and waste pickers. This understanding provide insights into how integration of waste pickers into separation-atsource programmes should be designed to maximize resident participation
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science (Geography and Environmental Studies), 2018
Keywords: Recycling (Waste, etc.)-South Africa; Integrated solid waste management